2017
DOI: 10.1016/j.jconrel.2017.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Sustained epidermal powder drug delivery via skin microchannels

Abstract: Transdermal delivery of hydrophilic drugs is challenging. This study presents a novel sustained epidermal powder delivery technology (sEPD) for safe, efficient, and sustained delivery of hydrophilic drugs across the skin. SEPD is based on coating powder drugs into high-aspect-ratio, micro-coating channels (MCCs) followed by topical application of powder drug-coated array patches onto ablative fractional laser-generated skin MCs to deliver drugs into the skin. We found sEPD could efficiently deliver chemical dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 36 publications
0
44
0
Order By: Relevance
“…When inserted into the skin, shafts of the MNA melted away in 10–15 min, exposing the powder to the epidermis (Figure 1D, 2hr). The powder sucked interstitial fluids from the skin tissue, dissolved slowly, and diffused into the epidermis over time against the interstitial fluid influx similarly to the powder drained into laser-generated microchannels previously demonstrated [19,20,28]. The powder was spreading horizontally into the epidermis and then vertically into the upper dermis (Figure 1D).…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…When inserted into the skin, shafts of the MNA melted away in 10–15 min, exposing the powder to the epidermis (Figure 1D, 2hr). The powder sucked interstitial fluids from the skin tissue, dissolved slowly, and diffused into the epidermis over time against the interstitial fluid influx similarly to the powder drained into laser-generated microchannels previously demonstrated [19,20,28]. The powder was spreading horizontally into the epidermis and then vertically into the upper dermis (Figure 1D).…”
Section: Resultsmentioning
confidence: 62%
“…Deposition of all the powder into the skin is not necessary for efficient delivery of the powder by powder-laden MNA, because the powder can be drained into the skin by the interstitial fluid influx. In this regard, our recent study demonstrated that powdered substance fractionally coated on a patch could sufficiently enter the skin even if the powder-coated patch was topically placed on a perforated skin [28]. The unique property of powder being drained into the skin by the interstitial fluid can thus permit a delivery of a high amount of vaccines or drugs via MNA, for instance, by extension of the basal cave above the skin as shown in our recent publication [28], which scores another advantage over traditional dissolvable and vaccine-coated MNAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike allergens in a liquid form, powdered allergen could be drained into the epidermis by sucking interstitial fluid from the skin tissue and diffusing against the interstitial fluid influx similarly to the powder draining into laser-generated microchannels previously demonstrated. 27 Therefore, even if the powder was encircled within the stratum corneum at the outermost layer or above the skin because of incomplete insertion, the powder could still enter the skin.…”
Section: Fabrication and Characterization Of Pld-mnasmentioning
confidence: 99%
“…17,[24][25][26] The powder was retained within the epidermis for an extended period of time, constantly stimulating the immune system for days. [25][26][27] In addition, we identified CpG, an agonist of Toll-like receptor 9 for T H 1 immune responses, and 1,25-dihydroxyvitamin D3 (VD3), an immunosuppressant, to be a potent tolerogenic adjuvant when combined. 17 To tailor this powder delivery technology for clinical uses, we recently engineered powder-laden, dissolvable microneedle arrays (PLD-MNAs) that could be directly applied onto intact skin to deliver powdered antigens into the epidermis 26 without the need for a laser to perforate the skin.…”
mentioning
confidence: 99%